Oral health promotion in elementary schools in Pinheiro, MA (Research, Society and Development, 2022)
Many children at school have problems with their developing teeth, due to the lack of access to information and dental services, thus making adequate and preventive care difficult. In view of this, the study was developed with the objective of discussing the importance of the promotion and prevention of oral health in elementary school in Pinheiro, MA. Therefore, a descriptive bibliographic research was carried out, based on the search for publications from 2017 to 2021 in the Scielo and Google Scholar databases, using the descriptors “health education”, “oral health” and “oral health education”. In order to relate the discourses and theoretical findings, a field research was carried out using a questionnaire via Google Forms, with managers and/or coordinators of public schools in the municipality of Pinheiro, MA. For discursive questions, Bardin's discourse analysis technique was used. As a result, it was found that school managers have been working in the schools in the sample for, on average, two and a half years; health education actions take place annually and are part of the Health Department's initiatives; there is no training for the school team, specifically on oral health, nor interdisciplinary projects on this topic. Nonetheless, when oral health actions take place the school community actively participates. Therefore, the importance of developing an interdisciplinary project and training and/or improvement of the school team was considered as strategies to promote oral health education in these schools.